Sagrado marfim: o império português na Índia e as relações intracoloniais Goa e Bahia, século XVII - iconografias, interfaces e circulações - Silva, Jorge Lúzio Matos (2011)
The maritime expansion of the Kingdom of Portugal overseas which resulted in the discoveries of Portuguese America and the ocean routes to Africa and Asia, produced the flow of a commercial network that constituted the Portuguese Colonial Empire. Intra-colonial relations were created and from these emerged a multicultural commercial exchange that determined the cultural roundness and permeability consequent of the traffic of navigators, missionaries and goods in the Atlantic and Indian Ocean. The latter also served in promoting a deep interaction between East and West through the daily routines of the ports and ships, with repercussions on practices and customs. This research examines ivory in the world Portuguese, from Africa to Índia through the Goa-Salvador intra-colonial relations in the Carreira da Índia so as to observe the impact of indo-portuguese iconography on ivory made in Índia and their influence in the local craftwork as brazilian material culture